Nonparametric threshold regression: Estimation and inference - HENDERSON, Daniel J. (Institutional Knowledge at Singapore Management University, 2015)
The present work describes a simple approach to estimating the location of a threshold/changepoint in a nonparametric regression. This model has connections both to the time-series and regressiondiscontinuity literatures. The estimator leverages a simple decomposition, giving it the form of asemiparametric smooth coefficient model. Optimal bandwidth selection and a suite of testing facilitiesare also presented. Several empirical examples are provided to illustrate the implementation of themethods discussed here.